Learning styles via interactive digital media: Malaysia history / Syahrini Shawalludin ...[et al.] - Shawalludin, Syahrini; Mohamed Salim, Neesa Ameera; Abdul Rahman, Azlan; Azman, Azlin; Mohamad Yunus, Fauziah (UiTM Press, 2020)
Interactive digital media refer to a product or service on the digital computer-based system, which responds to the user's action by presenting content inclusive of text, moving images, animations, and audio. This study aims to assess learner's perceptions and the feasibility of implementing interactive digital media (Malaysian History) and a guideline of designing interactive digital media to learning styles based on the Visual, Aural, Read or Write and Kinesthetic (VARK) model. This is a quantitative study which uses survey as a research design by distributing questionnaires to a total of 71 high school students residing in Kedah Darul Aman, Malaysia. Findings revealed that using interactive digital media in learning history is a significant digital tool in today's digital era, both in content and mechanics due to digital inclusion factor. This study justifies how digital and media research in the education landscape affects the learning styles and consequently instill interest in offering a deeper and more immersive learning experience.